The Pine Branch, January-February 1927 - (:unkn) unknown (Valdosta, Ga. : Writers Club of the Georgia State Womans College., 1927)
The Pine Branch, January-February 1927. Periodical magazine. Created and published by the Writers Club of the Georgia State Womans College, Valdosta, Georgia, 1927. Includes: editorials, photographs, poems, short stories, and other writings.
Modern Gypsies: E McRee 3 | The Unknown Quantity: Estha Freeman 6 | The Catalpa Tree: Mary Small 9 | That Familiar Number: Nell Bracey 10 | Why Is A Summer School?: E McRee 16 | Spring : Lucile Nix 20 | A Lord Chesterfield : Christine Meadows 21 | Editorial : Estha Freeman 26 | Y W C A Notes 28 | Society Notes 29 | Athletic Notes 31 | Locals 32 | Alumnae Notes 34 | Jokes 38 |
Keywords: College publications; College student newspapers and periodicals; Valdosta State University--Periodicals; Women; Women's colleges--Georgia--Valdosta; Georgia State Womans College; Valdosta; Schools--Georgia; Education